Industrial internet of things (IIoT) forensics: The forgotten concept in the race towards industry 4.0 - Victor R. Kebande (Forensic Science International: Reports, 2022)
Advances in Industrial Internet of Things (IIoT), inter-connectivity, continuous rise of smart ecosystems, and the quintessential need of process automation has not only opened formidable opportunities, but it has also extended the cyber-threat and attack landscape. Predominantly, this has been witnessed even as industries race towards aligning themselves with the on-demand industry 4.0 goals. Notably, it has become apparent that the convergence and amalgamation of Industrial Operational Technology (OT) with Information Technology (IT) brings about sophiscation, IIoT ecosystem complexities, paradigm shift and overall changes in security and digital forensic investigation architectures. Consequently, as the cybersecurity threat landscape also becomes more complicated in this context, with a widened attack surface, emergent and diverse system behaviors, the digital forensic perspective of IIoT is hardly integrated or addressed as many industries race to realize industry 4.0 objectives at the time of writing this paper. It is based on this premise, that this paper puts an argument that, at the time of writing this paper, there still lacks methodologies, standards, processes or maturity models that have a focus on IIoT forensics as the rat-race towards achieving Industry 4.0 persists. Based on these dimensions, the author explores the scope of IIoT forensics and posits the need of exploring and incorporating forensic standards and methods in IIoT. It is the authors’ opinion that the suppositions fronted herewith may provide fundamental building blocks for future IIoT-centered investigative frameworks.